Ownership concentration and firm performance in Indonesia - Juanda Juanda (Proceedings of AICS - Social Sciences, 2017)
The purpose of this paper is to investigate the influence of ownership concentration on the financial performance of firms listed on the Indonesian Stock Exchange from 2008 to 2012. The methodology used is multiple linear regression. The financial performance is measured with return on assets (ROA). The research shows that ownership concentration significantly and positively influences firm performance. This implies that the control of large shareholders is effective in enhancing firm performance of listed firms in Indonesia. This paper is particularly important to the policymakers of firms in Indonesia and other developing economies since it provides a comprehensive insight into the ownership concentration – firm performance relationship and therefore it helps them to formulate the best policies.